Changing landscapes of Southeast Asia and rodent-borne diseases: decreased diversity but increased transmission risks - Morand, Serge; Blasdell, Kim; Bordes, Frédéric; Buchy, Philippe; Carcy, Bernard; Chaisiri, Kittipong; Chaval, Yannick; Claude, Julien; Cosson, Jean-François; Desquesnes, Marc; Jittapalapong, Sathaporn; Jiyipong, Tawisa; et al. (Ecological applications, 2019)
The reduction in biodiversity from land use change due to urbanization and agricultural intensification appears to be linked to major epidemiological changes in many human diseases. Increasing disease risks and the emergence of novel pathogens result from increased contact among wildlife, domesticated animals, and humans. We investigated the relationship between human alteration of the environment and the occurrence of generalist and synanthropic rodent species in relation to the diversity and prevalence of rodent-borne pathogens in Southeast Asia, a hotspot of threatened and endangered species, and a foci of emerging infectious diseases. We used data from an extensive pathogen survey of rodents from seven sites in mainland Southeast Asia in conjunction with past and present land cover analyses. At low spatial resolutions, we found that rodent-borne pathogen richness is negatively associated with increasing urbanization, characterized by increased habitat fragmentation, agriculture cover and deforestation. However, at a finer spatial resolution, we found that some major pathogens are favored by environmental characteristics associated with human alteration including irrigation, habitat fragmentation, and increased agricultural land cover. In addition, synanthropic rodents, many of which are important pathogen reservoirs, were associated with fragmented and human-dominated landscapes, which may ultimately enhance the opportunities for zoonotic transmission and human infection by some pathogens.